An Engineered IgG–VHH Bispecific Antibody against SARS‐CoV‐2 and Its Variants. Issue 12 (27th October 2022) - Chi, Hang; Wang, Lei; Liu, Chanjuan; Cheng, Xiaohe; Zheng, Hailiang; Lv, Lilang; Tan, Yongcong; Zhang, Nana; Zhao, Suoqun; Wu, Mei; Luo, Dan; Qiu, Hongying; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) neutralizing antibodies are shown to be effective therapeutics for providing coronavirus disease 2019 (COVID‐19) protection. However, recurrent variants arise and facilitate significant escape from current antibody therapeutics. Bispecific antibodies (bsAbs) represent a unique platform to increase antibody breadth and to reduce neutralization escape. Herein, a novel immunoglobulin G–variable domains of heavy‐chain‐only antibody (IgG–VHH) format bsAb derived from a potent human antibody R15‐F7 and a humanized nanobody P14‐F8‐35 are rationally engineered. The resulting bsAb SYZJ001 efficiently neutralizes wild‐type SARS‐CoV‐2 as well as the alpha, beta, gamma, and delta variants, with superior efficacy to its parental antibodies. Cryo‐electron microscopy structural analysis reveals that R15‐F7 and P14‐F8‐35 bind to nonoverlapping epitopes within the RBD and sterically hindered ACE2 receptor binding. Most importantly, SYZJ001 shows potent prophylactic and therapeutic efficacy against SARS‐CoV‐2 in three established mouse models. Collectively, the current results demonstrate that the novel bsAb format is feasible and effective, suggesting great potential as an inspiring antiviral strategy. Abstract : A novel immunoglobulin G–variable domains of heavy‐chain‐only antibody (IgG–VHH) format bispecific antibody (bsAb) that confers protection against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and its variants are rationally developed. This universal platform combines the strengths of IgG and nanobody, provides a promising tool for the development of bsAbs, strongly complements and strengthens the existing SARS‐CoV‐2 antibody therapeutics.